A review on the magnetotelluric studies over the Central Asian Orogenic Belt—recent developments and future aspects - Li, Yifan; Zhang, Letian; Jin, Sheng; Zhou, Lishui; Zong, Qiyao (Frontiers in Earth Science, 2025)
The Central Asian Orogenic Belt (CAOB) was originated from the subduction, closure, convergence, and post-collisional extension of the Paleo-Asian Ocean located between the North China Craton, Tarim Craton, and the Siberian Craton during the late Permian to early Triassic. The Magnetotelluric (MT) method can detect the deep structure and properties of the orogenic belt, and further reveal the crust and mantle deformation mechanism and deep dynamic process inside the orogenic belt. In this paper, we summarize recent developments in the MT studies of the CAOB, including 2 MT studies that we recently conducted for the Beishan and Bainaimiao segments of the CAOB, which briefly describe the complex electrical structure of the crust and upper mantle, and provide valuable information for understanding its deep processes and continental dynamic mechanisms. Finally, we summarize the general characteristics of the lithospheric electrical structure and formation mechanism of low-resistivity zones, based on which we look forward to future MT studies.